A new population of Polyommatus ripartii (Freyer, 1830) in South Italy (Lepidoptera: Lycaenidae) - Rijllo, Giuseppe; La Cava, Sara; Zucco, Giada; Luzzi, Giuseppe; Coppola, Donata; Ferraro, Luciano; Scalercio, Stefano (Fragmenta entomologica, 2025)
In the present study, we recorded the presence of Polyommatus ripartii (Freyer, 1830) in a new area, enlarging the range of this species in southern Italy. Previously recorded only in the Pollino National Park, where it was initially described as a different species, a new population was discovered northward in the Appennino Lucano-Val d’Agri-Lagonegrese National Park.